Restorative approaches in hypodontia: clinical decision-making and treatment planning - Alhaqbani, Tarfah Saleh; Alsultan, Firas Mohamed; Al-Johani, Samer Masad; Alzahrani, Wael Ibrahim; Alshehri, Ayed Mohammed; Alshehri, Fayez Aied; Alkhayyal, Abdulrahman Kamal; Alqahtani, Fahad Saeed; Bahkali, Rahma Mohammed; Al Dossary, Saeed Saleh (International Journal Of Community Medicine And Public Health, 2025)
Individuals with one or more missing teeth are referred to as having hypodontia. In practice, maintaining emotional balance, aesthetic appeal, and psychological well-being can be extremely stressful. Managing hypodontia requires a collaborative effort involving prosthodontists, orthodontists, periodontists, and restorative dentists. This review discusses evidence-based restorative approaches for managing hypodontia within a patient-centered framework. These include conservative bridgework, conventional fixed prostheses, removable partial dentures, and implant-borne restorations. The treatment of choice depends on the extent of hypodontia, occlusal relationships, available alveolar bone volume, and the patient’s age. Orthodontic intervention is often necessary to achieve proper space distribution before definitive restoration and may also be required for interim prosthodontic rehabilitation. Digital advancements, such as computer-aided design, computer-assisted diagnosis, and 3D imaging, are critical in enhancing diagnostic precision, treatment planning, and prosthetic fabrication. Biological factors, including the integrity of periodontal tissues, occlusal forces, and long-term stability, are essential in determining the appropriate restorative approach. Additionally, patient-centered factors such as aesthetic expectations, treatment costs, and long-term maintenance play a decisive role in treatment selection. Modern approaches prioritize minimally invasive techniques and bioactive restorative materials to preserve tooth structure and improve outcomes. This review provides a structured protocol for managing hypodontia, emphasizing technological innovations, interdisciplinary collaboration, and patient-driven treatment planning. Advances in biomaterials, adhesive materials, and implant therapy continue to support clinical strategies for hypodontia, ensuring functional and aesthetically durable solutions.